Globalization, Democracy and Oil Sector Reform in Nigeria - Akinola, Adeoye O. (African Histories and Modernities, 2018)
The Nigerian state has been oil-rich for decades, and yet perennially incapable of converting its oil resources into wealth for ordinary Nigerians. Adeoye O. Akinola tackles this "vexed" oil question by examining the political economy of efforts to deregulate the Nigerian downstream oil industry. Focusing on themes of globalization and democratization, this book considers how a resource-rich developing country like Nigeria can exploit the opportunities of globalization and navigate the pressures of democratization and the challenges of liberalization. Pairing sophisticated theoretical frameworks with firsthand accounts from actors in the oil industry, this book identifies the root causes of Nigeria's development struggles and offers practical policy solutions for successfully deregulating the oil sector. For public officials and policymakers as well as researchers, this book offers a critical new lens on the future of natural resource management in Nigeria and the Global South.